Teak (Tectona grandis Linn) derived dye: an eco-friendly alternative for Eosin in histological staining - Manage, T.B.M.; Dhanapala, K.M.R.I.; Mahinda, M.T.R.; Rasaratnam, K. (University of Jaffna, 2024)
Introduction: Staining plays a pivotal role in the morphological evolution of tissue samples in histopathology. The combination of Hematoxylin and Eosin is the most common stain utilized for tissue staining. Hematoxylin, a nuclear stain, is a natural dye, whereas eosin is a synthetic dye. The use of synthetic dyes raises concerns about their harmful effects on both laboratory workers and the environment. Consequently, finding an alternative eco-friendly natural dye to replace eosin is inevitable to improve the laboratory diagnosis in histopathology. Objective: To evaluate the staining efficacy of a dye isolated from Tectona grandis Linn. on tissue samples. Methodology: Young leaves of T.grandis Linn. were collected and washed with tap water. The cleaned leaves were subjected to drying in an oven at 40°C and ground into fine powder. The extract was obtained by combining the dry plant material with 96% ethanol at 60°C for 4 hours and allowed at 25°C for12 hours. The mixture was filtered through Whatman paper followed by centrifugation at 5000 rpm for 15 minutes. The collected supernatant was removed using a Rotary evaporator and redissolved in absolute methanol to a final concentration of 20mg/ml. The staining ability of the dye was evaluated on 5 μm thick sections of human appendix tissues. Results: The findings demonstrated that the dye isolated from young leaves of Teak exhibits a staining potential on appendix tissues. Particularly, the staining ability of T. grandis Linn derived dye at a concentration of 20 mg/ml on tissue samples was comparable to those stained by Eosin. Conclusion: A dye extracted from T. grandis Linn. exhibits notable staining potential on histological tissues which could be utilized as an alternative eco-friendly natural stain for histological staining.
Keywords: Staining; Tectona grandis Linn; Histological tissues; Dye; Eosin